Designing Pirposal-learning based Module integrated with Socio-Scientific Issue to Enhance Students’ Scientific Reasoning Skill - Septaria, Kiki; Fatharani, Atika; Dewanti, Binar Ayu; Najawa, Wilda Choiryn (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
The purpose of this study is to explain the development of a Pirposal-learning based module that integrates with Socio-Scientific Issue (SSI) to enhance students’ scientific reasoning skill. This study is included in a mix method research, using Borg and Gall development and one group pretest and posttest design. Experts validate the development process, and its efficacy is measured using pre-test and post-test question sheets. Findings of the development of the learning module reached a validation score that was classified as very feasible; the results of the implementation of the learning module were seen through the realization of learning that was carried out very well, an increase in the average N-Gain of student scores, which the N-Gain was obtained by 0.701 with a high category. Furthermore, the results of calculations using the paired sample t-test show that the designed learning module considerably improves students’ scientific reasoning skill. Based on the findings, it is possible to infer that the Pirposal-learning based module that integrates with Socio-Scientific Issue (SSI) is an excellent learning media for training junior high school students in scientific reasoning skill.